Non-monotonic cell differentiation pattern on extreme wettability gradients - Cantini, Marco (2013)
In this study, we propose a methodology to obtain a family of biomimetic substrates with a hierarchical rough topography at the micro and nanoscale that span the entire range of wettability, from the superhydrophobic to the superhydrophilic regime, through an Ar-plasma treatment at increasing durations. Moreover, we employ the same approach to produce a superhydrophobic-to-superhydrophilic surface gradient along centimetre-length scale distances within the same sample. We characterize the biological activity of these surfaces in terms ofprotein adsorption and cell response, using fibronectin, a major component of the extracellular matrix, and C2C12 cells, a myoblast cell line. Fibronectin conformation, assessed via binding of the monoclonal antibody HFN7.1, exhibits a non-monotonic dependence on surface wettability, with higher activity on hydrophilic substrates (WCA = 38.6 ± 8.1°). On the other hand, the exposition of cell-binding epitopes is diminished on the surfaces with extreme wetting properties, the conformation being particularly altered on the superhydrophobic substrate. The assessment of cell response via the myogenic differentiation process reveals that a gradient surface promotes a different response with respect to cells cultured on discrete uniform samples: even though in both cases the same non-monotonic differentiation pattern is found, the differential response to the various wettabilities is enhanced along the gradient while the overall levels of differentiation are diminished. On a gradient surface cells are in fact exposed to a range of continuously changing stimuli that foster cell migration and detain the differentiation process.